Implementasi Jual Beli dalam Perikatan Syari’ah dan Konvensional - Septiana, Evy; Mahmudah, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
Along with the development of technology, people work together to create convenience in conducting transactions or muamalah, one of them is in term of buying and selling. Today, people can buy goods without coming directly to the seller. This certainly facilitates people for tricking. For these reasons, this research was conducted to understand the difference between Islamic and conventional practice on buying and selling engagements. This descriptive qualitative study employed literature study which obtained the result that even though the rules of all goods may be sold, but in Islam, it must not be contradicted with the quran, hadith, and benefit principle. Whereas, in conventional engagement, all goods can be absolutely sold, as long as there is willingness from both parties.